1980
DOI: 10.1152/ajpgi.1980.238.1.g23
|View full text |Cite
|
Sign up to set email alerts
|

Latency of pancreatic enzyme response to intraduodenal stimulants

Abstract: In six dogs with pancreatic fistulas, secretin (500 ng . kg-1 . h-1) was given to provide a flow of pancreatic juice of about 1 drop/s. Amylase concentration was measured in each drop before and after rapid intraduodenal injection of L-tryptophan, sodium oleate, and NaCl or after rapid intraportal injection of cholecystokinin (CCK). Latency of response (time between injection and a sustained increase in amylase output greater than the mean + 3 SD of prestimulation output) was 0.30 min to tryptophan and 0.33 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
2

Year Published

1983
1983
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 0 publications
6
45
2
Order By: Relevance
“…It is assumed that these effects of distension are mediated by reflexes lying within the vagus nerves from knowledge of similar responses in anaesthetized animals (Abrahamsson, 1973;Andrews et al 1980 a) and the fact that the events described in this paper were not influenced by either a-or ,-adrenergic blocking agents, nor were they altered by guanethidine (T. Scratcherd, unpublished observation). Although the experimental protocol prevented the accurate assessment of response latency it is clear (for example, Figs 1 and 4) that responses occurred within the circulation time as measured by the injection of CCK into the canine portal vein (Singer, Soloman & Grossman, 1980); a hormonal mechanism therefore seems unlikely though hormones could modify the response.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that these effects of distension are mediated by reflexes lying within the vagus nerves from knowledge of similar responses in anaesthetized animals (Abrahamsson, 1973;Andrews et al 1980 a) and the fact that the events described in this paper were not influenced by either a-or ,-adrenergic blocking agents, nor were they altered by guanethidine (T. Scratcherd, unpublished observation). Although the experimental protocol prevented the accurate assessment of response latency it is clear (for example, Figs 1 and 4) that responses occurred within the circulation time as measured by the injection of CCK into the canine portal vein (Singer, Soloman & Grossman, 1980); a hormonal mechanism therefore seems unlikely though hormones could modify the response.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the presence ofa secretin background, the shortest latency ofthe response to intraduodenal tryptophan or oleate was greater than that following intraportal secretin or CCK octapeptide (which probably represents the minimal circulation time of either hormone). In an earlier study (Singer et al 1980b) the latency of the amylase response to intestinal instillation of oleate (20 s) or tryptophan (18 s) was found to be shorter than that to intraportal injection of CCK (34 s). Since truncal vagotomy and atropine increased the latency of the enzyme response to both intestinal stimulants but not to intraportal CCK it was concluded that a vago-vagal, cholinergic reflex mediates the early pancreatic enzyme responses to intestinal amino acids and fatty acids.…”
Section: Discussionmentioning
confidence: 85%
“…However, recent studies (Singer, Solomon & Grossman, 1980a;Singer, Solomon, Rammert, Caspary, Niebel, Goebell & Grossman, 1981;Solomon & Grossman, 1979) in dogs with a transplanted extrinsically denervated portion of pancreas indicate that an enteropancreatic, vago-vagal, cholinergic reflex is a major mediator of the pancreatic enzyme response to intestinal stimulants such as amino acids, fatty acids and HCl. In another recent study (Singer, Solomon, Wood & Grossman, 1980b), further evidence for the existence of such a reflex was provided by comparing the latency of amylase secretion by the intact innervated pancreas in response to intestinal stimulants with that in response to an intraportal injection of cholecystokinin (CCK). The latency of the amylase response to intraduodenal oleate and tryptophan was shorter than to intraportal CCK.…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, however, the latency of the response of pancreatic outflow due to increased secretin release caused by intraduodenal injection of 30-50 ml of 0.4°c HC1 is about 2 min (BAYLISS and STARLING, 1902). SINGER et al (1980) also reported in vagotomized dogs that the latencies of the increased amylase output due to CCK release by intraduodenal stimulants, sodium oleate and tryptophan, are about 3 min. 2) There are some differences in the time courses of the responses by the short reflex and endogenous secretin.…”
Section: Discussionmentioning
confidence: 95%